Organic bioactive medicinal ingredients with antibacterial, anti-inflammatory and antioxidant properties - Cristina Dumitrache; Maria Crivineanu; Mihaela Eremia; Diana-Mihaela Alexandru (Medicamentul Veterinar, 2023)
The formulation of cosmeceutical products containing plant and animal compunds is the current concern of many researchers in the pharmaceutical field and it is the subject of many specialized studies. Natural active ingredients from the oleoresins and vegetable sources are frequently used in the field of cosmeceuticals due to their medical properties, among which the most important are the antibacterial, antifungal, anti-inflammatory and antioxidant action. In this mini-review, we presenetd the bioactive ingredients obtained from the resins of the Boswellia species, their general characteristics and the mechanisms of action by which the analyzed compounds can produce a beneficial effect. Due to the demonstrated effectiveness, numerous cosmeceutical products contain compounds obtained from the resins of Boswellia species.